Synthesis, Properties, and Applications of Polysulfone/Polyimide Nanocomposite Membrane Reinforced with Silica Nanoparticles. Issue 5 (5th August 2018) - Muntha, Sedra Tul; Ajmal, Muhammad; Naeem, Hina; Kausar, Ayesha; Zia, Muhammad Abid; Siddiq, Muhammad
Abstract : We synthesized polysulfone/polyimide nanocomposite membranes by solution casting method and reinforced with silica nanoparticles by in situ and ex situ techniques. Physical characteristics of nanocomposite membranes were explored by using X‐ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The appropriate ratio of polysulfone and polyimide was revealed through structural analysis. Thermal analysis revealed highest degradation temperature of 580°C for silica reinforced nanocomposite membrane as compared to that of neat polysulfone membrane which was found to be 500°C. On the other hand, glass transition temperature was found to be 85°C for neat polysulfone membrane which was improved to 205°C for polysulfone/polyimide blend membrane with an indication of better compatibility of glassy polymers. Young's modulus of neat polysulfone membrane was 3565.368 MPa which was increased to 5689.035 MPa for polysulfone/polyimide blend membrane and further increased to 7590.340 MPa for silica reinforced polysulfone/polyimide blend membrane. Membrane properties such as porosity and solvent content values were also explored. The antibacterial properties of fabricated nanocomposite membranes were investigated against Klebsiella pneumonia and Salmonella typhi . Better killing results were obtained against bacteria for PSf/PI/SiO2 nanocomposite membrane. POLYM. COMPOS., 40:1897–1910, 2019. © 2018 Society of Plastics Engineers